2003
DOI: 10.1002/jcu.10150
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler findings in middle cerebral arterial occlusive disease in relation to degree of stenosis and presence of concomitant stenoses

Abstract: ABSTRACT:Purpose. We evaluated the accuracy of transcranial Doppler (TCD) criteria in detecting middle cerebral artery (MCA) stenoses other than solitary severe stenoses.Methods. Three TCD criteria were evaluated in patients with acute MCA territory infarction who also underwent angiography: abnormalities in mean velocity (MV), focal areas of spectral waveform abnormalities, and compensatory increase in MV in collateral vessels.Results. Among 102 patients studied, angiography revealed MCA lesions in 48: 16 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The literature search originally identified 30 articles, 6 out of which (3 prospective and 3 retrospective) fulfilled our criteria for systematic review [12,13,14,17,18,19]. TC2-62 EME [12, 13], TC22, TC2000 [14], Multigon and Multidop [17] and Transcan EME [18, 19] were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search originally identified 30 articles, 6 out of which (3 prospective and 3 retrospective) fulfilled our criteria for systematic review [12,13,14,17,18,19]. TC2-62 EME [12, 13], TC22, TC2000 [14], Multigon and Multidop [17] and Transcan EME [18, 19] were used.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous articles have been published dealing with the accuracy of transcranial Doppler (TCD) in the diagnosis of a stenosis of the middle cerebral artery (MCA) [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40]. In these reports, different diagnostic criteria and velocity thresholds for the MCA stenosis yielded variable sensitivity and specificity parameters.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were identified with evidence of Ͼ70% ICA stenosis by color-coded sonography 9 or MCA stenosis (or occlusion) by transcranial Doppler (TCD) sonography. 10 Fifty-one patients had hemispheric transient ischemic attack (n ϭ 34) or other minor deficits (n ϭ 17), including weakness on 1 side of the body, reduced vision, or dizziness within 1 month before the MR imaging examination. Five patients with unilateral asymptomatic ICA occlusion were included (3 men, 2 women).…”
Section: Patientsmentioning
confidence: 99%
“…Some previous studies showed that an MFV of 80 cm/s or higher was an accurate transcranial Doppler sonographic criterion for evaluating large anterior circulation artery stenosis. [8][9][10][11][12] Other studies, however, concluded that the value of the PSV may be more accurate for assessing cerebral artery stenosis. 6,7 In this study, we found that a PSV of 120 cm/s or higher was an accurate criterion for diagnosing anterior circulation artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] There are no internationally accepted criteria for diagnosing intracranial stenosis. Furthermore, the diagnostic accuracy of predefined transcranial Doppler sonographic criteria for assessing intracranial stenosis has not yet been confirmed completely.…”
mentioning
confidence: 99%